Value Added Tax in Nepal: An Empirical Assessment - Shah, R. K. (Tribhuvan University Journal, 2010)
In developing economies, resource gap is critical and widening resulting tohuge fiscal and budgetary deficits. Therefore, revenue mobilization is challenging proposition in an economy like Nepal where majority of the people live in abject poverty. Tax administration lacks innovative mechanism to identify new tax payers and bring them into tax-net. Tax reform agenda was the reform package and program of the government after the restoration of multiparty democracy system. In Nepal, VAT was introduced in 1997 to improve revenue mobilization through broadening the tax base and modernizing the tax system. In this process, the government had to face new problems that came along with the adoption of VAT. Thus, the purpose of this study is to analyze the structure and responsiveness of VAT in Nepal empirically and compare it with that of old system of sales taxes. The old system of sales taxes refers to the combined sales, entertainment, contracts, hotels, and air flight taxes received by the government before 1997/98.